Reproduction and resistance in a university graduate program of adult education: Developing ideological space for program transformation - Phyllis Cunningham; Glenn Smith (Adult Education Research Conference, 1994)
This study explored transformation within a graduate program. The data support the conclusion that ideological space and program transformation can be forged to support a non dominant ideology and resulting diversity in the student body. Transformation triggered countering regulatory processes within the university but not in the faculty.